2016
DOI: 10.1371/journal.pone.0158403
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Oilseed Rape Fields and Feral Populations in the Context of Coexistence with GM Crops

Abstract: Despite growing concern about transgenes escaping from fields, few studies have analysed the genetic diversity of crops in an agroecosystem over several years. Accurate information about the dynamics and relationship of the genetic diversity of crops in an agroecosystem is essential for risk assessment and policies concerning the containment of genetically modified crops and their coexistence with crops grown by conventional practices. Here, we analysed the genetic diversity of oilseed rape plants from fields … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 49 publications
1
25
0
Order By: Relevance
“…Glucosinolate levels are known to vary both within and across Brassica populations (Hopkins, van Dam & van Loon 2009), yet little is known about chemical traits in feral oilseed rape. A subset of our feral populations displayed relatively high GS levels, which could have arisen as a result of founder effects (populations originating from high-GS cultivars), natural selection and/or hybridization (e.g., Charters, Robertson & Squire 1999;Pessel et al 2001;Bond et al 2004;Pivard et al 2008;Elling, Neuffer & Bleeker 2009;Pascher et al 2010;Schulze et al 2014;Bailleul, Ollier & Lecomte 2016). The relative importance of these nonmutually exclusive processes in shaping trait variation remains largely unresolved (Elling, Neuffer & Bleeker 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glucosinolate levels are known to vary both within and across Brassica populations (Hopkins, van Dam & van Loon 2009), yet little is known about chemical traits in feral oilseed rape. A subset of our feral populations displayed relatively high GS levels, which could have arisen as a result of founder effects (populations originating from high-GS cultivars), natural selection and/or hybridization (e.g., Charters, Robertson & Squire 1999;Pessel et al 2001;Bond et al 2004;Pivard et al 2008;Elling, Neuffer & Bleeker 2009;Pascher et al 2010;Schulze et al 2014;Bailleul, Ollier & Lecomte 2016). The relative importance of these nonmutually exclusive processes in shaping trait variation remains largely unresolved (Elling, Neuffer & Bleeker 2009).…”
Section: Discussionmentioning
confidence: 99%
“…While theoretical models have aimed at addressing this outstanding issue (Claessen et al 2005;Garnier & Lecomte 2006), demographic data encompassing the entire life cycle are scarce (Pessel et al 2001;Bagavathiannan & Van Acker 2008;Pascher et al 2010; but see : Crawley et al 1993;Crawley & Brown 1995;Crawley & Brown 2004;Hooftman et al 2015). This is an important knowledge gap as oilseed rape is a major crop for which transgenic lines have been developed (Ellstrand, Prentice & Hancock 1999;Hails & Morley 2005;Warwick et al 2008;Schafer et al 2011;Bailleul, Ollier & Lecomte 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In an assessment of five study areas and 20 growing seasons, it was concluded that the distribution and persistence of feral B. napus is possible but the proportion of the population overall and their contribution to adventitious mixing is negligible [18]. Two studies both noted that feral populations of cultivars were not of the dominant genotype currently being grown in adjacent fields [55,56]. They showed instead to have greatest similarity with the cultivar grown the previous year.…”
Section: Crop Growthmentioning
confidence: 99%
“…They showed instead to have greatest similarity with the cultivar grown the previous year. Several studies have suggested that feral plants often survive for just one year even when self-seeding the previous year was prolific [54,55]. For example, it has been found that, in a given year, 35%-40% of feral B. napus plants resulted from the movement of seed from the adjacent field during the previous year [57].…”
Section: Crop Growthmentioning
confidence: 99%
See 1 more Smart Citation